2022
DOI: 10.1177/00104140221074283
|View full text |Cite
|
Sign up to set email alerts
|

Negative Campaigning and Vote Choice in Europe: How Do Different Partisan Groups React to Campaign Attacks?

Abstract: Parties spend parts of their campaigns criticizing other parties’ performance and characteristics, such as honesty, integrity, and unity. These attacks aim to negatively affect the target parties’ electoral performance. But do they work? While attacks are informative, we argue that how voters react to negative campaigning depends on their partisanship. While the target’s copartisans are more likely to get mobilized in favor of their party, the attacker’s copartisans are expected to punish the target due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Further research needs to account for this heterogeneous relationship between party, campaign tone and electoral success – particularly keeping in mind that the targets of political attacks, which we were unable to investigate here, are likely to matter as well. Increasing evidence shows that the dynamics of attack politics are interactive ones (Dolezal et al, 2016; Somer-Topcu and Weitzel, 2020), and that the effectiveness of political attacks depends on the characteristics of both the sponsor of the attacks and their target.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Further research needs to account for this heterogeneous relationship between party, campaign tone and electoral success – particularly keeping in mind that the targets of political attacks, which we were unable to investigate here, are likely to matter as well. Increasing evidence shows that the dynamics of attack politics are interactive ones (Dolezal et al, 2016; Somer-Topcu and Weitzel, 2020), and that the effectiveness of political attacks depends on the characteristics of both the sponsor of the attacks and their target.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Two underlying gaps can be identified. First, parties are incentivised to attack on policy and/or trait to obtain vote (e.g., Somer‐Topcu & Weitzel, 2022) and office (e.g., Walter et al., 2014) goals during campaigns, whereas outside campaigns, policy goals also become relevant (e.g., Otjes & Louwerse, 2018). In other words, while in campaigns parties attack their rivals expecting to gain support of the electorate ( vote ) and a potential seat in the cabinet ( office ), outside campaigns, they may also engage in attacks trying to, for example, place issues high on the agenda (Green‐Pedersen & Mortensen, 2010) or secure ownership over an issue (Walgrave & De Swert, 2007).…”
Section: Parties’ Attack Behaviour In Parliamentsmentioning
confidence: 99%
“…Attacks between political actors can take place on several levels (between individuals, parties, group of parties), but they are always driven by the underlying party competition logic, in which vote (e.g., Somer‐Topcu & Weitzel, 2022), office (e.g., Walter et al., 2014) and policy (e.g., Otjes & Louwerse, 2018) goals are the main objectives. For example, recent studies have shown that attacking actors on policies may lower voters’ perceptions of the targeted actor (Lefevere et al., 2020; Seeberg & Nai, 2021).…”
Section: Parties’ Attack Behaviour In Parliamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studying partisanship in this context is important, because it can lead to variability in individual reactions to campaigns (Druckman et al, 2019;Fridkin & Kenney, 2011). Research on the role of partisanship investigated negative campaigning as an umbrella term rather than specifically uncivil campaigning and deceitful campaign techniques (e.g., Haselmayer et al, 2020;Nai, 2013;Somer-Topcu & Weitzel, 2022).…”
Section: Introductionmentioning
confidence: 99%